Dendritic cells: professional antigen presenting cells - Fairchild, Paul J. (Henry Stewart Talks, 2021)
Differentiation of dendritic cells from hematopoietic progenitors, Classification of dendritic cell subsets, Dendritic cell maturation and migration patterns, Outcomes of DC-T cell interactions, The therapeutic use of dendritic cells